Problem and Competence Development Design of State Civil Apparatus (ASN) in Banggai District through Education and Training Activities - KISMAN KARINDA; ERWIN NURSIN (Jurnal Studi Pemerintahan, 2018)
By using quantitative research approach, this study discloses that education and training activities for ASN competence development has a positive influence on ASN employees performance, in which ASN in the area of Banggai District government has a good skill and knowledge in performing his/her duties and obligations as an ASN including: Firstly, ASN employees act consistently and transparently in accordance with the condition of local government organization.  Secondly, ASN employee acts on the applicable laws and regulations.  Thirdly, ASN employees are able to put forward an adaptive leadership in every situation and condition of the government.  Fourthly, ASN employees have innovation in performing their duties and obligations as an ASN.  Fifthly, ASN employees have motivation in executing duties and functions of local government organization. Thus, education and training activities of ASN employees’ competence development has to continuously perform focused on the development of knowledge and the reinforcement of ASN’s skill.